Shopping Experience of Hypermarket Shoppers on Weekends - Atulkar, Sunil; Kesari, Bikrant (Indian Journal of Marketing, 2016)
Improving the retail customer shopping experience in hypermarkets, especially in weekends is a key to enhance the performance of retail stores. The present research focused on hypermarket shoppers to measure the customer shopping experiences with different dimensions of customer shopping experiences by establishing a research framework based on 366 user responses. Confirmatory factor analysis and structural equation modeling (SEM) were used to analyze and validate the proposed research framework. The paper is a first of its kind to discuss the various dimensions of customer shopping experience, especially in Bhopal city (Central India). The research findings showed that the customer shopping experiences are unpredictable and are positively influenced by enjoyment, emotional attachment, comfort, uniqueness, and impulsiveness dimensions of customer shopping experiences. Therefore, this study would help hypermarket retailers to focus on these constructs, which are considered as an important dimension of the customer shopping experience, and would help the retailers in gaining a competitive advantage, attracting new customers, and to hold their profitable customers by enhancing customer shopping experiences in the current retail scenario.